2018
DOI: 10.31665/jfb.2018.2140
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary extract as a natural source of bioactive compounds

Abstract: Rosemary (Rosmarinus officinalis, L.) is an aromatic evergreen herb widely used around the globe as a spice/seasoning, flavoring agent and for medicinal applications. Rosemary extract derived from rosemary leaves contains several polyphenolic components which exhibit antioxidant properties, but the predominant active components are the phenolic diterpenes, namely, carnosic acid and carnosol. Over 90% antioxidant activity of rosemary extract is attributed primarily to high content of lipophilic antioxidant mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…In many areas, rosemary is a commercial spice that has attracted attention due to its antioxidant and therapeutic properties. [10,11] On the other hand, Rosmarinus is applied as a food preservator because have antioxidation and antimicrobial activity. [12] Zataria multiflora Boiss is a member of the Lamiaceae family that grows geographically in Iran, Pakistan and Afghanistan .…”
Section: Introductionmentioning
confidence: 99%
“…In many areas, rosemary is a commercial spice that has attracted attention due to its antioxidant and therapeutic properties. [10,11] On the other hand, Rosmarinus is applied as a food preservator because have antioxidation and antimicrobial activity. [12] Zataria multiflora Boiss is a member of the Lamiaceae family that grows geographically in Iran, Pakistan and Afghanistan .…”
Section: Introductionmentioning
confidence: 99%
“…Syringic acid that was identified in this work is also found in nuts, fruits, culinary herbs, and their processing by-products (Alvarez-Parrilla et al, 2018;Mirfat et al, 2018;Senanayake, 2018;Shahidi and Hossain, 2018). In contrast, while several feedstocks show catechin in their phenolic profile (Amarowicz and Shahidi, 2018;Silva et al, 2018;Silva et al, 2019), the presence of gallocatechin is not as common.…”
Section: Total Phenolics and Maldi-tof-ms Analysismentioning
confidence: 51%
“…Previous studies have demonstrated that cooked salmon devoid of antioxidants showed higher TBARS values compared to samples cooked in the presence of butylated hydroxyanisole or phenolic extracts from different natural sources (Albishi et al, ; de Camargo et al, ). Rosemary is rich in phenolic antioxidants such as carnosic acid and carnosol (Senanayake, ). According to da Silva et al () , increased TBARS values were detected in blue catfish subjected to smoking, which was lower in rosemary extract‐treated samples.…”
Section: Resultsmentioning
confidence: 99%